PENGENDALIAN KUALITAS SARUNG TANGAN GOLF BRENCE MENGGUNAKAN STATISTICAL QUALITY CONTROL DAN KANSEI DI CV. CAHAYA SETIA MULIA ABADI - Fani Nugroho; Widya Setiafindari (JURNAL MULTIDISIPLIN ILMU AKADEMIK, 2026)
This study analyzes defect levels, evaluates process stability, identifies potential causes, and develops quality-control recommendations for Brence golf gloves at CV. Cahaya Setia Mulia Abadi. Observation data and production records from January to March 2026 were documented using a daily check sheet covering 51 observations, including output quantities and mis-cut, hole, and thread-residue defects. The data were then analyzed using histograms, a p-control chart, a Pareto diagram, fishbone analysis, and a Kansei approach. Of 15,000 units produced, 917 units were defective, representing 6.11%. Mis-cut defects were dominant with 511 units (55.73%), followed by thread residue with 252 units (27.48%) and holes with 154 units (16.79%). Mis-cut defects and thread residue accounted for 83.21% of all defects. The p-control chart produced a center line of 0.06113; two observations indicated special-cause variation: the defect proportion of 0.03375 on January 2, 2026 was below the LCL of 0.03572, while the proportion of 0.21000 on March 17, 2026 exceeded the UCL of 0.11196. Fishbone analysis grouped potential causes into human, equipment/machine, method, material, and work-environment factors. The Kansei words were neatness, precision, cleanliness, smoothness, strength, and comfort. Recommendations include a maximum four-hour continuous cutting rotation, equipment inspection at least twice per shift, a maximum of two material layers for curved cutting sections, final inspection, a maximum thread residue of 2 mm, and needle inspection or replacement at least every eight hours. Their effectiveness should be tested with post-implementation production data.